How Clothes Make the Woman Immoral: Impressions Given Off by Sexualized Clothing. (July 2013) - Montemurro, Beth; Gillen, Meghan M.
The goal of the present study was to examine clothing as a marker of women's sexuality. Ninety-five women in their 20s - 60s participated in in-depth interviews. Many women reported concern with sexual messages others might perceive from their clothing, and judged other women's clothing on the dimensions of authenticity, morality, and appropriateness. Self- and other- clothing judgments varied by the target's age, marital status, and parental status, and for other-judgments, by social class and generation. Results suggest that women's bodies are socially monitored and that sexual subjectivity is suppressed through the stigmatization of women's sexualized dress.